A lakosság riasztása és a magatartási szabályok . The early warning of the public and the rules of conduct in emergency - Polgári Védelem Országos Parancsnokság (Polgári Védelem Országos Parancsnokság, 1975)
Air raid warning constitutes an important part of civil defense. Because of the constant threat from the aggressive imperialist powers, the sirens can go off at any time. This why we need to know more about civil defense. In the course of our preparations for emergency situations, civil defense training founded on the principle of mutual assistance receives special emphasis. Organized defense can only be effective if the whole country is aware of the manner of warning and if the warning signal reaches everyone. This has made Kossuth Radio a crucial factor in the country's civil defense. A légiriasztás a civilek védelmének kulcsfontosságú része. Az agresszív imperialista fenyegetés miatt bármikor megszólalhatnak a szirénák. Ezért fontos a polgári védelmi ismereteinket tökéletesítenünk. A veszélyhelyzetekre való felkészítés során nagy hangsúlyt kap a polgári védelmi oktatás, mely a kölcsönös segítségnyújtás elvére épül. A szervezett védelem csak akkor hatásos, ha az egész ország tisztában van a riasztás módjaival és ha a vészjelzés mindenkihez eljut. Ezáltal vált polgári védelmi tényezővé a Kossuth Rádió.